Trinidad. After a day’s work. Hindu charcoal sellers - (:unkn) unknown (My University, 2010)
A charcoal seller of East Indian descent, driving his donkey cart at the end of a work day. He is accompanied by his female companion and a dog.
Colour: Black and white; Style: Landscape;Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Donkeys; Men; Women--East Indian; Dogs; Draft animals